Comparing the outcomes of two independent computed tomography perfusion softwares and their impact on therapeutic decisions in acute ischemic stroke. (18th May 2020) - Bathla, Girish; Ortega-Gutierrez, Santiago; Klotz, Ernst; Juergens, Markus; Zevallos, Cynthia B; Ansari, Sameer; Ward, Caitlin E; Policeni, Bruno; Samaniego, Edgar; Derdeyn, Colin
Abstract : Background: To compare the computed tomography perfusion (CTP) outcomes derived from two commercial CTP processing software and evaluate their concordance in terms of eligibility for mechanical thrombectomy (MT) in acute ischemic stroke (AIS), based on DEFUSE III criteria. Methods: A total of 118 patients (62 patients in the MT group and 56 patients in the non-MT (NMT) group) were included. Volumetric perfusion outputs were compared between Syngo.via (package A) and RAPID (package B). Influence on proceeding or not-proceeding with MT was based on DEFUSE III imaging eligibility criteria. Results: Median core infarct/hypoperfusion volumes were 12.3/126 mL in the MT group and 7.7/29.3 ml in the NMT group with package A and 10.5/138 mL and 1.9/24.5 mL with package B, respectively. In the MT group (n=62), concordant perfusion results in terms of patient triage were noted in all but two cases. Of these, one patient would not have qualified (low ASPECTS), while the other qualified based on package A results. For the NMT group (n=56), there was discordance in terms of MT eligibility in seven cases. However, none of these patients qualified for MT based on DEFUSE III criteria. Conclusions: Both perfusion softwares showed high concordance in correctly triaging patients in the MT versus NMT groups (110/118, 93.2%), which further improved when all DEFUSE III imaging criteria were considered (117/118, 99.1%). The core/hypoperfusion volumes in the NMT group and core infarct volumes in the MT groups were comparable. The hypoperfusion volumes in the MT group varied slightly but did not affect triage between groups.